The Development of the Urban Network in Slovakia - Mezei, István (Discussion Papers, 2012)
The settlement structure of Slovakia is the result of long historical development. In the first part of the paper, the author presents the towns according to their population, ethnic and occupational composition in Felvidék (Upper Hungary) before 1918. In the second part the most important factors that have influenced the development of town network are described (Slovak conquest, town planning, administration, economy and education). In the final chapter the Hungarian and Slovak borderland region with towns at all levels of development is characterized.